2016
DOI: 10.1128/aem.00795-16
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Zoonotic Enteropathogens in Children and Domestic Animals in a Semirural Community in Ecuador

Abstract: Animals are important reservoirs of zoonotic enteropathogens, and transmission to humans occurs more frequently in low-and middle-income countries (LMICs), where small-scale livestock production is common. In this study, we investigated the presence of zoonotic enteropathogens in stool samples from 64 asymptomatic children and 203 domestic animals of 62 households in a semirural community in Ecuador between June and August 2014. Multilocus sequence typing (MLST) was used to assess zoonotic transmission of Camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 41 publications
1
57
3
Order By: Relevance
“…33 This community was selected for the study because it is characterized by high levels of small-scale livestock production, and research has documented a high prevalence of zoonotic enteric infections in children. 34 The sampling frame for this study consisted of all households in OtĂłn de Velez with a child under 5 years of age in which the household reported raising livestock. Research conducted by a member of the research team during the previous year identified approximately 60 households to be within this sampling frame.…”
Section: Methodsmentioning
confidence: 99%
“…33 This community was selected for the study because it is characterized by high levels of small-scale livestock production, and research has documented a high prevalence of zoonotic enteric infections in children. 34 The sampling frame for this study consisted of all households in OtĂłn de Velez with a child under 5 years of age in which the household reported raising livestock. Research conducted by a member of the research team during the previous year identified approximately 60 households to be within this sampling frame.…”
Section: Methodsmentioning
confidence: 99%
“…e G. duodenalis prevalence in male rabbits (11.5%) (95% CI: 7.70-15.33) was slightly higher (χ 2 ïżœ 0.05, df ïżœ 1, P ïżœ 0.82) than that in female rabbits (11.0%) (95% CI: 7.67-14.22) ( Table 2). In the present study, the overall G. duodenalis prevalence in rabbits was 11.2% (69/616), which was higher than that in rabbits in Henan province (8.4%, 80/955) [15], Jilin province and Liaoning province (9.86%, 42/426) [18], Heilongjiang province (7.41%, 28/378) [20], Xinjiang province (1.9%, 6/ 321) [19] in China, and in Europe (7.6%, 40/528) [16] and Melbourne, Australia (1.03%, 1/97) [22], but lower than that in rabbits in Ecuador (20.0%, 4/20) [17]. e different G. duodenalis prevalence in rabbits may be caused by many factors such as geographical ecological environment, detection methods, sample size, and individual health status [23].…”
Section: E Prevalence Of G Duodenalis In Rabbitsmentioning
confidence: 99%
“…Rabbits are one of the most important economic animals in China, and the consumption of meat and fur accounts for a large part of China's economy [12]. However, rabbits are susceptible to many pathogens [5,13,14], including G. duodenalis [15][16][17][18][19][20], which can cause significant economic losses to the rabbit breeding industry.…”
Section: Introductionmentioning
confidence: 99%
“…The same inflammation-mediated mechanisms via which this gut disorder-termed environmental enteric dysfunction (EED)-is thought to stunt linear growth (Humphrey, 2009;Prendergast et al, 2014) could be integral to its role in the aetiology of anaemia in children (Morceau, Dicato, & Diederich, 2009;Prendergast et al, 2015). If children are especially susceptible to the pathogenic bacteria associated with livestock production (Osbjer et al, 2016;Vasco, Graham, & Trueba, 2016), this may explain why children, but not women, from livestock owning households were more likely to be anaemic.…”
Section: Consumption Of Asfs and Associations With Livestock Ownersmentioning
confidence: 99%